Image Processing and Communications Challenges 3 - Choras, Ryszard S. (Springer eBooks., 2011)
This book was written to inform prospective readers of current trends in image processing and communications area. Image processing and communications represent a dynamic part of computer science, playing increasingly important role in an information era. This book presents the new approaches, in: image processing and computer vision; telecommunications networks, Web-based  information systems; mathematical methods for these applications. This book is a collection of carefully selected chapters presenting the fundamental theory and practice of various aspects of image data processing and communications. The book consists of two sections: 1.       Image processing 2.       Communications. The image processing section of this book provides an inside on mainly on theories and methodologies as well as the emerging applications of image processing. Various aspects of new trends and techniques in this field are discussed in the book, covering the following topics: - Biometrics - Low level processing - Motion, stereo and tracking - Pattern Recognition - Video - Medical Image Analysis - Applications. The book summarises new developments in these topics.